IMPLEMENTASI FOUR EYES PRINCIPLE PADA BANK KALBAR SYARIAH CABANG SAMBAS - Devi lestari (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
Bank is a business entity that collects funds from the public in the form of savings and distributes them to the public in the form of credit and/or other forms in order to improve the standard of living of the people at large.Islamic banks or commonly referred to as interest-free banks, are banking institutions whose operations and products are developed based on the Al-Qur'an and the Hadith of the Prophet SAW. In other words, Islamic banks are financial institutions whose main business is providing financing and other services in payment traffic and money circulation whose operations are in accordance with Islamic sharia principles.In developing countries like Indonesia, bank activities, especially in lending, are one of the most important and main bank activities so that income from credit is the largest income. Therefore the risk of loss from lending is also large, so to avoid large risks, banks must apply the Four Eyes Principle system. This research uses a type of descriptive qualitative research, which only describes situations and events that come from interviews and observations. The benefit of this research is to find out whether the four eyes principle has been properly implemented at the Sambas Branch of the Sharia Bank Kalbar. The results of this study indicate that so far the Sambas Branch Sharia Bank Kalbar has implemented the Four Eyes Principle in banking activities carried out by the Sambas Branch Sharia Bank, it has been proven that so far there have been no problems or obstacles faced by the Sambas Branch Sharia Bank in channeling financing / credit.